Influences of perpendicular compressive stress on the dielectric and ferroelectric properties of electrostrictive and piezoelectric Pb (Mg1/3 Nb2/3) O3 -PbTiO3 ceramics - Muangjai Unruan (2018)
The dielectric and ferroelectric properties of (1-x) Pb (Mg1/3 Nb2/3) O3 - (x) PbTiO3 or (1-x) PMN- (x) PT (x=0.1-0.4) ceramics were measured under compressive stress applied perpendicular to the electric field. For the dielectric properties, the experimental results revealed that the superimposed perpendicular compression stress reduced the dielectric constant but increased the dielectric loss tangent of all the compositions. On the other hand, for the ferroelectric properties the applied stress noticeably enhanced the dissipation energy, the polarizations, and the coercive field of all the compositions. These results were interpreted through the non- 180° ferroelastic domain switching processes, the stress clamping of domain walls, the deaging mechanism, and the stress induced enhancement in the switchable part of spontaneous polarization. More importantly, the influences of the stress applied in the perpendicular direction to the electric field were generally opposite to those of the parallel stress. © 2008 American Institute of Physics.